2001
DOI: 10.4319/lo.2001.46.4.0765
|View full text |Cite
|
Sign up to set email alerts
|

Direct use of inorganic colloidal iron by marine mixotrophic phytoplankton

Abstract: Three species of photosynthetic flagellates capable of phagotrophy (mixotrophic species) were tested for their abilities to use inorganic iron colloids for growth. Ochromonas sp., Chrysochromulina ericina (a coastal strain), and C. ericina (an oceanic strain) were grown in iron-free seawater supplemented with 1 M Fe-ferrihydrite (amorphous hydrous ferric oxide), magnetite (Fe 3 O 4 )/maghemite (␥-Fe 2 O 3 ), hematite (␣-Fe 2 O 3 ), or goethite (␣-FeOOH). Desferrioxamine B, an iron-binding siderophore, was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 54 publications
4
74
2
Order By: Relevance
“…Ingested iron minerals are subjected to low pH processing in the gut that enhances bioavailability. Nodwell and Price (2001) showed that some species of mixotrophic flagellates were able to use goethite, haematite and magnetite but not ferrihydrite, whilst other species could only use ferrihydrite. In all cases uptake appeared to involve ingestion and thus represents the direct use of colloidal iron by eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ingested iron minerals are subjected to low pH processing in the gut that enhances bioavailability. Nodwell and Price (2001) showed that some species of mixotrophic flagellates were able to use goethite, haematite and magnetite but not ferrihydrite, whilst other species could only use ferrihydrite. In all cases uptake appeared to involve ingestion and thus represents the direct use of colloidal iron by eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hassler and Schoemann (2009) found no direction link between soluble and bioavailable Fe because organic ligands have the differential effects on the solubility and the bioavailability. Several studies seem to suggest that organic colloidal Fe provides an important pool to sustain Fe bioavailability to phytoplankton (e.g., Nodwell and Price, 2001;Chen et al, 2003;Wang and Dei, 2003). Finally, icebergs themselves could have other effects on NPP.…”
Section: Correlation Between Annual Npp and Small Iceberg Frequencymentioning
confidence: 99%
“…This anomalous retention of denser minerals could reveal the biological interaction of iron particles with microorganisms described by some authors (Nodwell and Price 2001, Sohm 2011, Benavides et al 2013. Under the sedimentological point of view, this anomalous "low sinking behaviour" of the densest iron oxyhydroxide particles is another innovation presented in this research.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have shown that phagotrophic flagellates could ingest even micrometric iron particles or colloids, dissolving and regenerating some types of particulate iron during digestion (Barbeau et al 1996, Chase and Price 1998, Barbeau and Moffett 2000, and retaining the mineral in the water column (Nodwell and Price 2001). Moreover, it has been suggested that colony formation in Trichodesmium is an adaptive strategy to trap the dust and enhance iron acquisition (Rubin 2011), dissolving dust and oxides.…”
Section: Mineralogymentioning
confidence: 99%